2022
DOI: 10.3390/jpm12020307
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Robotic Visceral Surgery in Patients with Adhesions: A Systematic Review and Meta-Analysis

Abstract: Abdominal adhesions are a risk factor for conversion to open surgery. An advantage of robotic surgery is the lower rate of unplanned conversions. A systematic review was conducted using the terms “laparoscopic” and “robotic”. Inclusion criteria were: comparative studies evaluating patients undergoing laparoscopic and robotic surgery; reporting data on conversion to open surgery for each group due to adhesions and studies including at least five patients in each group. The main outcomes were the conversion rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 109 publications
(333 reference statements)
0
10
0
Order By: Relevance
“…Moreover, two conversions from laparoscopy were described by Draaisma et al [ 27 ], and two conversions from the robotic approach were reported by Morino et al and Nakadi et al [ 32 , 34 ]. Although nowadays the risk of conversion to open surgery has decreased due to higher surgeon expertise, it is important to underline that the conversion rate from robotic surgery is lower than that from laparoscopy, according to current literature [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two conversions from laparoscopy were described by Draaisma et al [ 27 ], and two conversions from the robotic approach were reported by Morino et al and Nakadi et al [ 32 , 34 ]. Although nowadays the risk of conversion to open surgery has decreased due to higher surgeon expertise, it is important to underline that the conversion rate from robotic surgery is lower than that from laparoscopy, according to current literature [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the procedures performed by “expert surgeons” showed a statistically significant difference in favor of robotic surgery (OR 1.48, 95% CI 1.03-2.12, p = 0.03). A reduced conversion rate due to adhesions with the robotic approach was observed in patients undergoing colorectal cancer surgery (OR 2.62, 95% CI 1.20-5.72, p = 0.02) ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Park et al 44 reported that previous abdominal surgery did not worsen the perioperative outcomes of either laparoscopic or robotic colorectal surgery. Milone et al 45 examined 70 studies that performed 14,329 minimally invasive procedures (6,472 robotic and 7,857 laparoscopic) in patients with adhesions and reported that the robotic approach was associated with a significantly lower risk of conversion (P = 0.007). In addition, the conversion rate was low in patients who underwent colorectal cancer surgery in the robotic group (P = 0.02).…”
Section: Patients With Abdominal Adhesionsmentioning
confidence: 99%